2010
DOI: 10.3892/ol.2010.187
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic subtype-specific genomic profiles of renal cell carcinomas identified by high-resolution whole-genome single nucleotide polymorphism array analysis

Abstract: Abstract.To elucidate the novel and common genetic changes in histopathologic subtype-specific profiles of renal cell carcinomas (RCCs), a newly developed high-resolution wholegenome array analysis was applied. Human CNV370-Duo DNA Analysis BeadChip (genotype 370K) was used in a panel of 22 primary clear cell RCCs (ccRCCs), seven papillary RCCs (PRCCs) (six type II and one type I) and eight chromophobe RCCs (ChRCCs). In ccRCC, a chromosome 3p loss was identified in 95% of the carcinomas, suggesting that 3p los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We have previously reported that each RCC subtype has a totally different genetic profile by whole genome SNP array [10]. Therefore, each subtype should have a specific biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that each RCC subtype has a totally different genetic profile by whole genome SNP array [10]. Therefore, each subtype should have a specific biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…RCC consists of clear cell (75%), papillary (10%), chromophobe (5%) and other subtypes [10], and we first focused on clear cell carcinoma, the most common subtype of RCC. We discovered a significant increase of circulating plasma FN1 in patients with RCC and confirmed its significance in a larger patient cohort using a newly established measurement system.…”
Section: Introductionmentioning
confidence: 99%